Adakite-like parental melt generation by partial fusion of juvenile lower crust, Sakarya Zone, NE Turkey: a far-field response to break-off of the southern Neotethyan oceanic lithosphere - Karsli, Orhan; Schmitt, Axel Karl (Lithos, 2019)
The timing of major tectonic events and the driving mechanisms for magma generation during Late Cenozoic convergence and collision between Arabia and Eurasia still remain unknown. The Sakarya Zone (SZ) in northern Turkey is a critical member of this collisional assemblage. In the easternmost part of the SZ, we have recognized a Late Miocene volcanic suite termed the Çağirankaya volcanics which displays characteristic post-collisional geochemical features. Here, we report a new data set of zircon UPb ages, whole-rock major and trace element, as well as SrNd isotope analyses for dacite and andesite samples from the Çağirankaya volcanics. Zircon UPb ages for a selected dacitic lava sample average 5.16±0.11Ma (mean square of weighted deviates, MSWD=0.45, n=35), confirming a late Miocene age of this volcanic episode. The high-K calc-alkaline andesites and dacites exhibit an adakite-like geochemical signature, and are characterized by high Sr (424 to 552ppm), Sr/Y ratios (31-43), and low Mg# (42 to 46) values, along with low Y (12-14ppm) and heavy rare earth element (HREE) concentrations, that resemble those in adakites formed by partial melting of hot oceanic slab during subduction. Isotopic compositions are near bulk Earth (87Sr/86Sr(t)=0.70482 to 0.70489, εNd(t)=+1.08 to +1.33), which rules out a solely asthenospheric origin. Elevated Nb/Ta (14 to 17) and K2O/Na2O (0.6-1.0) imply a juvenile mafic lower crustal source composed of ~20% garnet-bearing amphibolite. Geochemical modeling suggests that adakite-like parental melts were generated in the absence of subduction and without large-scale delamination of lower continental crust. Instead, our findings suggest that Late Miocene adakite-like volcanic rocks in the SZ formed in a post-collisional intra-continental setting, which experienced far-field extension after the subducted slab of the southern Neotethyan branch became detached in the collision zone. Asthenospheric upwelling and underplating of basaltic magma provided the heat for partial melting of lower crustal amphibolite, forming minor amounts of adakite-like melts in the SZ.
Gesehen am 11.07.2019